Systematic review and meta-analysis of specific external Chinese herbal medicines for post-stroke dysphagia: efficacy and clinical implications - Zhang, Jingwen; Kang, Xingyu; Zhao, Jingwen; Niu, Jiajie; Chen, Siyu; Shi, Shuai (Frontiers in Pharmacology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of specific external traditional Chinese medicine therapies (SETCM therapies) versus conventional non-SETCM therapy interventions for improving swallowing function, nutritional status, and reducing complications in adult patients with post-stroke dysphagia (PSD), based on randomized controlled trials (RCTs).MethodsA comprehensive search was conducted from inception to present across Chinese [(China National Knowledge Infrastructure (CNKI), VIP Chinese Science and Technology Periodical Database (VIP), Wanfang Data Knowledge Service Platform (WFSD), Chinese Biology Medicine Database (CBM)] and international databases (PubMed, Embase, Web of Science, and Cochrane Library). RCTs investigating validated SETCM therapy modalities (e.g., herbal patches, iontophoresis, compresses, and fumigation) for PSD were included. All herbal components were taxonomically validated using the Kew Medicinal Plant Names Service (MPNS). The control group received conventional therapy (rehabilitation, nursing, and medication). The experimental group received SETCM therapies alone or combined with conventional care. The risk of bias in eligible studies was assessed using the Cochrane risk-of-bias tool. A meta-analysis was performed using RevMan 5.4. Stratified subgroup analyses were conducted based on stroke lesion location (supratentorial vs. brainstem) and intervention type.ResultsTwenty-five RCTs (n = 2,159 patients; SETCM therapies group = 1,152, control group = 1,007) were included. The meta-analysis demonstrated significantly greater benefits in the SETCM therapies group for: overall response rate (OR = 3.28, 95% CI [2.49, 4.31]); overall cure rate (OR = 2.36, 95% CI [1.84, 3.02]); water swallowing test (WST) score (MD = −0.65, 95% CI [−1.23, −0.06]); and SWAL-quality-of-life (SWAL-QOL) score (MD = 25.61, 95% CI [20.54, 30.67]). The SETCM therapies group also demonstrated superior results in videofluoroscopic swallow study (VFSS) scores, modified Barthel index (MBI), serum albumin (ALB), prealbumin (PA), gugging swallowing screen (GUSS), activities of daily living (ADL), and functional dysphagia scale (FDS) scores, nasogastric tube removal success rate, as well as lower Nutritional Risk Screening 2002 (NRS 2002) scores, reduced aspiration incidence, and shorter nasogastric tube indwelling time. Safety analysis (three studies) reported mild skin irritation (erythema and pruritus) in 2.1% of cases.ConclusionSETCM therapies significantly improved swallowing function, nutritional status, and clinical outcomes in patients with PSD. Efficacy exhibited neuroanatomical specificity: Acupoints are preferred for cerebral hemisphere lesions, while herbal iontophoresis is the best choice for brainstem involvement. These findings support the integration of targeted SETCM therapies into PSD rehabilitation. However, the evidence is limited by methodological biases, necessitating high-quality RCTs for confirmation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024599344.